Penerapan Enkripsi dan Dekripsi Dokumen Data UMKM Menggunakan Algoritma ChaCha20-Poly1305 - Widjaya, I Made Chandra; Mogi, I Komang Ari (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 1 (2024): JNATIA Vol. 3, No. 1, November 2024DO - 10.24843/JNATIA.2024.v03.i01.p14, 2024)
Despite the increasing importance of data security in safeguarding sensitive information, this study addresses the potential risks associated with unauthorized access to critical data. Employing the ChaCha20-Poly1305 algorithm, the research focuses on implementing encryption and decryption processes for Small and Medium Enterprise (SME) documents, supplemented by key derivation from AES-256 for enhanced security. A nonce Initialization Vector (IV) is generated using the ChaCha20-Poly1305 algorithm, with users inputting secret keys for encryption. The system then encrypts the data using the ChaCha-Poly1305 algorithm and derives keys from AES using SHA-256 hashing. For decryption, users input the encrypted document into the program, along with the previously used key. The system design employs a simple web-based application, with the ChaCha20-Poly1305 cryptography algorithm implemented in PHP. The study successfully tests the ChaCha20-Poly1305 algorithm and the program exhibits secure decryption processes, evidenced by consistent byte sizes of tested SME documents.